Exploratory Factor Analysis as a Tool for Determining Indicators of a Research Variable: Literature Review - Sappaile, Baso Intang; Abeng, Andi Tenri; Nuridayanti, Nuridayanti (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. Exploratory factor analysis can be used as a guideline for constructing instrument homogeneity. Purpose. Factor analysis is the queen of analytical methods because of its strength, flexibility and closeness to the nature of scientific aims and objectives. Method. Roughly speaking, an instrument whose items measure only one trait in general and can determine the indicators of a research variable. To determine the number of indicators based on eigenvalues greater than or equal to one, both in the initial factor analysis and in further analysis. Results. A statement item is declared eligible for inclusion in a factor if the item has a factor load greater than or equal to 0.30 on only one factor. Similarly, an indicator is declared feasible if its factor load is greater than or equal to 0.30. Conclusion. The item that has the highest factor load on a factor contributes the most to that factor, so that item is used as the basis for guidance in naming a factor as the name of the indicator.